Porphyromonas gingivalis adopts intricate and unique molecular mechanisms to survive and persist within the host: a critical update. Issue 1 (1st January 2020) - Chopra, Aditi; Bhat, Subraya G.; Sivaraman, Karthik
ABSTRACT: Porphyromonas. gingivalis (P. gingivalis): is an obligate, asaccharolytic, gram-negative bacteria commonly associated with increased periodontal and systemic inflammation. P. gingivalis is known to survive and persist within the host tissues as it modulates the entire ecosystem by either engineering its environment or modifying the host's immune response. It interacts with various host receptors and alters signaling pathways of inflammation, complement system, cell cycle, and apoptosis. P. gingivalis is even known to induce suicidal cell death of the host and other microbes in its vicinity with the emergence of pathobiont species. Recently, new molecular and immunological mechanisms and virulence factors of P. gingivalis that increase its chance of survival and immune evasion within the host have been discovered. Thus, the present paper aims to provide a consolidated update on the new intricate and unique molecular mechanisms and virulence factors of P. gingivalis associated with its survival, persistence, and immune evasion within the host.